Begonia cabanillasii (section Baryandra, Begoniaceae), a new species from El Nido, Palawan, the Philippines - Ang, Yu Pin; Tandang, Danilo N.; Agcaoili, John Michael M.; Bustamante, Rene Alfred Anton (Phytotaxa, 2020)
While assisting El Nido-Taytay Managed Resource Protected Area in their biodiversity monitoring of El Nido, Palawan, the authors came across a very distinctive and small population of Begonia. Based on careful investigation, the unknown species is confirmed as new to science, and is the latest addition to the species rich section Baryandra. A new species, Begonia cabanillasii is hereby described and illustrated. It is compared with phenetically similar species B. suborbiculata. Based on guidelines by IUCN, the new species is proposed to be Critically Endangered (CR) C2a.